2021
DOI: 10.7717/peerj.11410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of auxin transporter AUX, PIN and PILS gene families in pineapple and evaluation of expression profiles during reproductive development and under abiotic stresses

Abstract: Polar auxin transport in plant is mediated by influx and efflux transporters, which are encoded by AUX/LAX, PIN and PILS genes, respectively. The auxin transporter gene families have been characterized in several species from monocots and eudicots. However, a genome-wide overview of auxin transporter gene families in pineapple is not yet available. In this study, we identified a total of threeAcAUX genes, 12 AcPIN genes, and seven AcPILS genes in the pineapple genome, which were variably located on 15 chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…The relative expression level was detected by quantitative real time PCR (qRT-PCR) using the Bio-Rad QRT-PCR system (Foster City, CA, United States) and SYBR Premix Ex TaqII (TaKaRa Perfect Real Time; Zhang et al, 2020a ). The qRT-PCR program was: 95°C for 30 s; 40 cycles of annealing at 95°C for 5 s, and extension at 60°C for 35 s; 95°C for 15 s ( Zhang et al, 2020a ; Zhao et al, 2021 ). The rice OsUBQ5 gene was used as an internal control ( Jain et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…The relative expression level was detected by quantitative real time PCR (qRT-PCR) using the Bio-Rad QRT-PCR system (Foster City, CA, United States) and SYBR Premix Ex TaqII (TaKaRa Perfect Real Time; Zhang et al, 2020a ). The qRT-PCR program was: 95°C for 30 s; 40 cycles of annealing at 95°C for 5 s, and extension at 60°C for 35 s; 95°C for 15 s ( Zhang et al, 2020a ; Zhao et al, 2021 ). The rice OsUBQ5 gene was used as an internal control ( Jain et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since we treated the rice seedlings for 16 h and thereafter recorded PIN expression, it appears that a longer duration of heat treatment might downregulate PIN expression. Another study by Zhao et al (2021) in pineapple (Ananas comosus) revealed that the expression of AcPIN8 was upregulated under heat stress while AcPIN5a was downregulated. These observations indicate that the PIN expression is very dynamic, and they are differentially regulated in a PIN member-and plant species-dependent manner during heat stress.…”
Section: Discussionmentioning
confidence: 98%
“…Since we treated the rice seedlings for 16 h and thereafter recorded PIN expression, it appears that a longer duration of heat treatment might downregulate PIN expression. Another study by Zhao et al. (2021) in pineapple ( Ananas comosus ) revealed that the expression of AcPIN8 was upregulated under heat stress while AcPIN5a was downregulated.…”
Section: Discussionmentioning
confidence: 98%
“…In the study of Arabidopsis, light affects IAA synthesis during seedling germination, and IAA transport from developing leaves to roots ( Bhalerao et al, 2002 ). Auxin transport is usually mediated by auxin influx and efflux vectors, which are encoded by the AUX1/LAX , PIN , and PILS (PIN-LIKES) genes, respectively ( Zhao et al, 2021 ). Members of the AUX1/LAX gene family are major auxin influx carriers, and mutations in its gene cause auxin-related developmental defects and are involved in the regulation of key plant processes, including root, and lateral root development, root gravitation and hair development, vascular patterns, seed germination, leaf morphogenesis, and embryo development ( Swarup and Bhosale, 2019 ).…”
Section: Discussionmentioning
confidence: 99%